Monetary Policy, Inflation Illusion and the Taylor Principle – An Experimental Study - Wolfgang J. Luhan; Johann Scharler (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
We develop a simple experimental setting to evaluate the role of the Taylor principle, which holds that the nominal interest rate has to respond more than one-for-one to fluctuations in the inflation rate. In our setting, the average infl ation rate fluctuates around the inflation target if the computerized central bank obeys the Taylor principle. If the Taylor principle is violated, then the average infl ation rate persistently deviates from the target. We find that these deviations from the target are less pronounced, if inflation rates cannot be as readily observed as nominal interest rates. This result is consistent with the interpretation that subjects underestimate the influence of inflation on the real return to savings if the infl ation rate is only observed ex post. – – Wir entwickeln ein simples Experiment um die geldpolitische Rolle des Taylor Prinzips zu untersuchen. Das Taylor Prinzip besagt, dass der Nominalzins überproportional auf Schwankungen der Inflationsrate reagieren muss. In unserem Design oszilliert die durchschnittliche Inflationsrate um den Zielwert, falls die (automatisierte) Zentralbank dem Taylor-Prinzip folgt. Wird dieses verletzt, dann führt dies zu permanenten Abweichungen vom Inflationsziel. Nach unseren Ergebnissen sind diese Abweichungen weniger stark ausgeprägt, wenn die Inflationsrate weniger offensichtlich ist als die Nominalzinsen. Die Probanden unterschätzen teilweise den Einfluss der Inflationsrate auf die Realzinsen, wenn die Inflationsrate nur ex post beobachtet werden kann.
Keywords: E30; E52; C90; 330; Taylor principle; interest rate rule; inflation illusion; laboratory experiment